Neutrosophic Valued PID Controller for Closed Loop V/f Speed Control of Permanent Magnet Synchronous Motor - HAÇAT, Gülnur; ÇETİNCEVİZ, Yücel (Omer Halisdemir Universitesi, 2023)
In this article, a neutrophic logic-based closed loop V/f control system has been established by creating a fuzzy inference system and a neutrophic fuzzy logic controller (NFLC) in Matlab. Also, the NFLC-PID block diagram has been established to test in a Simulink environment with permanent magnet synchronous motor (PMSM). The simulation results demonstrate that the neutrosophic fuzzy logic controller managed the PMSM efficiently and successfully.